A novel navigation algorithm for hexagonal hexapod robot - Ahmed, Mohiuddin; Khan, Md. Raisuddin; Billah, Md. Masum; Farhana, Soheli (Science Publications, 2010)
Problem statement: Wheeled robots are not very well suited for navigation over uneven terrains. Hexapod robots have some advantages over wheeled robots when negotiating and navigating on rugged terrain. Approach: Different gaits of hexapods can be developed for different kinds of locomotion and obstacle avoidance. Results: In this research a novel algorithm has been developed for hexapod robots navigation. Conclusion: Implementation of the developed algorithm on a hexapod prototype showed desirable performance in terms of stable navigation with simultaneous gait transition over different terrains.